Renewable energy review :|barriers to renewable energy in developing countries - Mohammad, Saad. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Renewable energy has been a very trendy topic in recent decades not only in the developed world but also in the developing world. Considering the depleting fossil fuels and existential threats like Global Warming and Climate Change harnessing energy from renewable sources of energy is good bargain. In this study, first the renewable energy is reviewed in general and comprehensive information is provided for each major renewable source of energy. Second the barriers to the adoption of these renewable energy technology in developing countries are discussed and analyzed. Barriers found are compared by using the Analytical Hierarchy Process (AHP) as an analyzing tool. The most significant barriers for developing countries found are; Lack of financial mechanism, High Investment Requirement, Criminal and terrorist activities, Exclusion of environment externalities in cost, and Lack of standardization. Barriers like “Criminal and Terrorist activities” and Corruption, which have not been mentioned by many studies in the literature, are found to be very significant and moderately significant barrier respectively. The comparative analysis of this study with the existing literature shows that the achieved level of importance of the barriers differs when focusing on a particular region or country. For example, factors such as the political scenario in the country, economic situation, and geographical conditions have a different importance level for different regions or countries. The contribution provides general barriers for the adoption of renewable energy technology in developing countries around the world that could be used to help the government and investors take steps to help in removing or limiting the extent of these barriers.
Keywords: Renewable energy sources.